Direct and Indirect Testing for Accountability of Regional Financial Management and Trust Level of Public-Stakeholders in Local Government - Fuad, Khoirul; Winarsih, Winarsih (Jurnal ASET (Akuntansi Riset), 2021)
Every organization wants to be trusted by public-stakeholders. Their trust is a form of recognition for results, performance, and achievements. The authority of the central government to regional governments regarding financial management is a demand for improvement in all areas in order to achieve a goal and target from the central government, one of which is that all parties trust. Therefore, this study tries to connect several factors that can be used as indicators to achieve public trust, including the presentation and accessibility of regional financial reports, control activities carried out by local governments, and accountability of financial reports prepared by local governments. This study used a quantitative approach by distributing questionnaires to the 160 local bureaucracies (Indonesian: OPD which stands for Organisasi Perangkat Daerah) in Semarang. This study used structural equation modeling (SEM) with smart PLS. This study found that the presentation of financial reports, accessibility of financial reports, and control activities had a positive effect on the accountability of regional financial management. Besides, this research also found that the presentation of financial reports, accessibility of financial reports, control activities and accountability of regional financial management had a positive effect on public stakeholder trust. Furthermore, the accountability of regional financial management fully mediates the relationship between the presentation of financial statements, the accessibility of financial reports, and control activities on public-stakeholder trust.